5(x - 8) - 8(3x - 4)(6x + 8) = 5x - 40 - 8 [ 18x^2 + 24x -24 x -32 ] = 5x - 40 - 8 ( 18x^2 - 32 ) = 5x - 40 - 144 x^2 + 256 = -144 x^2 + 5x + 216
Simplify the following and collect the like terms:
5(x - 8) - 8(3x - 4)(6x + 8)
I know i have to do the foil thing for the last part but what do I do with the -8?
Cause from the first part you get:
5x - 40
Then I know I have to do the 3x * 6x then 3x * 8 then -4 * 6x and then -4 * 8.
Am I doing it wrong. Well I know I am but where does the -8 come into play.